Gut Microbiota and Its Implications for Cardiovascular Diseases – a Review - Zarębska, Julia; Krasnoborska, Julia; Samojedny, Sylwia; Superson, Maciej; Szmyt, Katarzyna; Szymańska, Katarzyna; Walczak, Kamil; Wilk-Trytko, Klaudia; Zarębski, Łukasz (Journal of Education, Health and Sport, 2024)
Background: The symbiotic relationship between the gut microbiota and cardiovascular health has become a main point in contemporary research, offering valuable insights into the pathogenesis of cardiovascular diseases (CVDs). This review aims to comprehensively examine the bidirectional communication between gut microbial communities and the cardiovascular system, explaining the intricate mechanisms that connect gut dysbiosis to the initiation and progression of CVDs. Material and Methods: A systematic literature review was conducted to compile and analyze relevant studies investigating the impact of the gut microbiota on cardiovascular health. Emphasis was placed on explaining the molecular and physiological mechanisms underlying the interaction between gut microbes and cardiovascular function. Results: Our review confirmed evidence linking gut microbiota-derived metabolites, such as short-chain fatty acids, trimethylamine N-oxide and lipopolysaccharides to vascular function and inflammation. Additionally, we explored the modulation of host metabolism and immune responses by gut microbes, providing insights into their roles in atherosclerosis and hypertension. The review highlight the influence of diet and lifestyle on shaping the gut microbiome and, consequently, cardiovascular outcomes. Conclusions: Gut microbiota plays a crucial role in cardiovascular health and is involved in the start and development of various heart diseases. The identified molecular and physiological mechanisms highlight the need for complete understanding of the gut-cardiovascular axis. Moreover, the review emphasizes the potential of microbiota-targeted interventions, including probiotics and fecal microbiota transplantation, as innovative strategies for preventing and managing CVDs.